Sex Differences in Brown Adipose Tissue Function: Sex Hormones, Glucocorticoids, and Their Crosstalk - Kaikaew, Kasiphak; Grefhorst, Aldo; Visser, Jenny A. (Frontiers in Endocrinology, 2021)
Excessive fat accumulation in the body causes overweight and obesity. To date, research has confirmed that there are two types of adipose tissue with opposing functions: lipid-storing white adipose tissue (WAT) and lipid-burning brown adipose tissue (BAT). After the rediscovery of the presence of metabolically active BAT in adults, BAT has received increasing attention especially since activation of BAT is considered a promising way to combat obesity and associated comorbidities. It has become clear that energy homeostasis differs between the sexes, which has a significant impact on the development of pathological conditions such as type 2 diabetes. Sex differences in BAT activity may contribute to this and, therefore, it is important to address the underlying mechanisms that contribute to sex differences in BAT activity. In this review, we discuss the role of sex hormones in the regulation of BAT activity under physiological and some pathological conditions. Given the increasing number of studies suggesting a crosstalk between sex hormones and the hypothalamic-pituitary-adrenal axis in metabolism, we also discuss this crosstalk in relation to sex differences in BAT activity.